Cerebellar correlates of visual hallucinations in Parkinson's disease and Charles Bonnet Syndrome. (February 2021) - Lawn, Timothy; ffytche, Dominic
Abstract: Hallucinations, percepts in the absence of external stimuli, are a shared feature of eye-disease (Charles Bonnet Syndrome, CBS) and Parkinson's disease (PD) thought to arise through pathophysiologically distinct mechanisms: deafferentation and attentional network dysfunction respectively. Recent studies have found an association between visual hallucinations and structural changes in the cerebellum without obvious link to either mechanism. Here, we employed Voxel Based Morphometry (VBM), optimised for the cerebellum using the Spatially Unbiased Infratentorial Template (SUIT), to characterise similarities and differences in cerebellar structure associated with visual hallucinations in PD and CBS. Grey and white matter volume (GMV & WMV) from patients with eye-disease (n = 12 hallucinators; n = 9 non-hallucinators) and PD (n = 7 hallucinators; n = 9 non-hallucinators) was examined in a 2-way ANOVA controlling for age, sex, and intracranial volume. Comparing hallucinators to controls across both groups, lower GMV was found bilaterally within cerebellar lobule VIII extending to IX/VII. GMV reductions were also found in Crus 1, greater in PD than eye-disease. Predominantly within PD, hallucination-related lower WMV was found in the medulla. No regions of increased GMV or WMV were found. A correlation was observed between brainstem WMV and lobule VIIIb GMV suggesting a functional association. Lobule VIII comprises a functional node within the Dorsal Attention Network (DAN), linking these findings to current attentional theories of hallucinations, while Crus 1 is linked to cortical visual processing. These findings provide preliminary evidence of a cerebellar contribution to hallucinations that transcends clinical conditions.